Assembly modelling through constraint-based manipulations in a virtual reality environment - Zhong, Yongmin; Shirinzadeh, B.; Ma, W.; Liaw, H. (IEEE, 2005)
With today’s irtual reality (VR) systems, it is difficult to create precise assembly models through 3D interactions due to hardware limitations. In this paper, an efficient approach is presented for intuitive and precise assembly modeling in a VR environment. Assembly modelling is performed by precise constraint-based 3D direct manipulations in an intuitive manner. Constraint-based manipulations are accompanied with automatic constraint recognition and precise constraint satisfaction, and are realized by allowable motions for precise 3D interactions in the VR environment. Some special constraint-based assembly operations are constructed for assembly modelling in the VR environment. A method for recognizing the pairs of mating features between assembly components is presented. This method integrates 3D direct manipulations with a feature mating knowledge base and makes the process of recognizing a pair of mating features intuitive. A concept of offset solid is also presented for determining assembly components. A prototype system has been developed for assembly modelling through precise constraint-based manipulations in an intuitive manner in the VR environment.